2011
DOI: 10.1245/s10434-011-1565-y
|View full text |Cite
|
Sign up to set email alerts
|

Does a Supplementary Preoperative Breast MRI in Patients with Invasive Lobular Breast Cancer Change Primary and Secondary Surgical Interventions?

Abstract: The implementation of preoperative breast MRI tended to result in more primary mastectomies and bilateral surgeries and did not seem to decrease the secondary surgery rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 26 publications
1
25
0
Order By: Relevance
“…Previous research examining the association between breast MRI and surgical outcomes for ILC patients found conflicting results regarding the benefit of breast MRI [5, 8, 18-20]. Our findings are similar to a meta-analysis among ILC patients which found that breast MRI was significantly associated with an increased likelihood of an initial mastectomy and weakly associated with a lower likelihood of a reoperation [8].…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…Previous research examining the association between breast MRI and surgical outcomes for ILC patients found conflicting results regarding the benefit of breast MRI [5, 8, 18-20]. Our findings are similar to a meta-analysis among ILC patients which found that breast MRI was significantly associated with an increased likelihood of an initial mastectomy and weakly associated with a lower likelihood of a reoperation [8].…”
Section: Discussionsupporting
confidence: 70%
“…Our results differed from the meta-analysis in that the meta-analysis reported that preoperative breast MRI was associated with an increased likelihood of a final mastectomy whereas we found that ILC patients with breast MRI were no more likely to have a final mastectomy than those ILC women who did not receive a preoperative breast MRI. Our results may differ because the included studies were single institution studies [18-20] and one RCT [5] which included only a small number of patients with ILC. Furthermore, these studies reflect surgical practices from single institutions or in the United Kingdom, where breast cancer treatment patterns, decision-making factors, health service/insurance structures, and fiscal considerations may be different than and not generalizable to the US elderly population.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Most recently, Heil et al 45 have contributed to the literature regarding outcomes in lobular cancer and found that MRI made no significant difference on the mastectomy rate (P = 0.119), no significant difference in the second surgery rate (P = 0.429) but it made a significant increase in bilateral procedure rate (P = 002, although the numbers were small N = 5).…”
Section: Impact On Treatmentmentioning
confidence: 99%